1998
DOI: 10.1001/archotol.124.7.794
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Postoperative Pain After Laryngeal Surgery for Cancer

Abstract: After laryngeal surgery for cancer, pain can reach high levels, particularly in the first hours following recovery. Analgesic administrations at fixed hours are not effective enough. Postoperative analgesic treatment should aim to prevent the high initial pain and be individually adapted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…However, a study performed in men having undergone a partial or total laryngectomy demonstrated that postoperative pain decreases with time (Mom et al, 1998). This practice allows for an appropriate pain management at the time the pain is the most severe in the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study performed in men having undergone a partial or total laryngectomy demonstrated that postoperative pain decreases with time (Mom et al, 1998). This practice allows for an appropriate pain management at the time the pain is the most severe in the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…The time course of pain intensity during this period is not completely known. However, a study performed in men having undergone a partial or total laryngectomy demonstrated that postoperative pain decreases with time (Mom et al, 1998). In addition, postoperative pain intensity course can be extrapolated from studies reporting the use of rescue medication, with the highest morphine consumption during the 6 h following surgery (Hernandez-Palazon et al, 2001;Fletcher et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Pharyngolaryngeal cancer surgery is associated with a high level of pain in the early postoperative period [1]. The IV route is the common way of providing postoperative analgesia for pharyngolaryngeal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Les chirurgies des cancers des VADS peuvent donner des douleurs postopératoires intenses, maximales dans les premières heures puis s'atténuant progressivement dans les 48 à 72 heures [2,3] (niveau de preuve 2). L'évaluation de la douleur doit tenir compte des difficultés ou de l'impossibilité de parler (trachéotomie, trachéostomie).…”
Section: Douleurs Postopératoires Précocesunclassified